Dynamics of Staphylococcus aureus in patients and the hospital environment in a tertiary care hospital in the Netherlands - Adriënne S. van der Schoor; Anne F. Voor in ’t holt; Willemien H.A. Zandijk; Marco J. Bruno; Diederik Gommers; Johannes P.C. van den Akker; Johanna M. Hendriks; Juliëtte A. Severin; Corné H.W. Klaassen; Margreet C. Vos (Antimicrobial Resistance and Infection Control, 2023)
Abstract Background The dynamics of Staphylococcus aureus in patients and the hospital environment are relatively unknown. We studied these dynamics in a tertiary care hospital in the Netherlands. Methods Nasal samples were taken from adult patients at admission and discharge. Isolates cultured from clinical samples taken before and during hospitalization from these patients were included. Environmental samples of patient rooms were taken over a three-year period. Finally, isolates from clinical samples from patients with an epidemiological link to S. aureus positive rooms were included. Staphylococcal protein A (spa) typing was performed. Results Nasal samples were taken from 673 patients. One hundred eighteen (17.5%) were positive at admission and discharge, 15 (2.2%) patients acquired S. aureus during hospitalization. Nineteen patients had a positive clinical sample during hospitalization, 15.9% of the S. aureus were considered as from an exogenous source. One hundred and forty (2.8%) environmental samples were S. aureus positive. No persistent contamination of surfaces was observed. Isolates were highly diverse: spa typing was performed for 893 isolates, identifying 278 different spa types, 161 of these spa types were observed only once. Conclusion Limited transmission could be identified between patients and the hospital environment, and from patient-to-patient. Exogenous acquisition was assumed to occur in 15% of clinical samples. Environmental contamination was infrequent, temporarily, and coincided with the strain from the patient admitted to the room at that time. MRSA was rare and not found in the environment.